LEFLUNOMIDE IN EARLY RHEUMATOID ARTHRITIS: INCLUSION IN THE TREATMENT STRATEGY AND PROSPECTS - D. E. Karateev; E. V. Orlova (Медицинский совет, 2017)
According to the literature, Leflunomide is comparable in efficacy and safety with methotrexate, including patients with early rheumatoid arthritis (RA). The drug continues to play an important role in the treatment of patients with early RA and may be considered as a main synthetic base anti-inflammatory drug which should be administered in case of impossibility of treatment by effective doses of methotrexate. The combination of Methotrexate and Leflunomide, reducing the need for biological therapy, may be an effective way to overcome tolerance to Methotrexate. The role of this combination treatment strategies for early RA may be underestimated, it is expedient to conduct further research in this direction.